A PROPOSAL FOR THE MANAGEMENT OF HUMAN COMPETENCES FOR SUSTAINABILITY - Barbara Galleli; Flavio Hourneaux Junior; Luciano Munck (Faces: Revista de Administração, 2020)
Considering the discussion regarding the need to promote and develop sustainability in organisations, this study aims to propose the management of human competences for sustainability. The study comprises two phases. First, after reviewing the theories and concepts related to competences and their relationship with sustainability in organisations, we defined six specific human competences. In the second phase, to ascertain the adherence of this set of competences in the organisations, two studies were conducted in companies that are recognized for their actions focused on sustainability and competences management. The evidence reinforces that the competence-based approach represents an appropriate perspective that strategicly drives sustainability management in organisations. As a proposal, the following aspects were defined based on a guiding model: what is the competence-based management model suitable for, how it will be developed, formatted and used.